Experiencia de producción audiovisual para proyectos de desarrollo - Gonzales Ramos, Daniel Anibal (2023)
Bachelor in Communication Sciences from the University of Lima, specializing in Audiovisual Production. I work professionally as a Producer, Video and 2D Animation Director, Graphic Designer and Audiovisual Postproducer of audiovisual materials that make visible the social projects of companies and non-governmental organizations. At the same time, I teach in Private Technological Institutes of Higher Education, I have been in charge of the subjects of Editing, Post-production, Graphic Design, Audiovisual Production and 2D Animation. I am a partner and founder of the audiovisual communication company Claxon Comunicaciones SAC. since 2014 and, through it, I have managed to consolidate my interest in making known in an audiovisual way, different social projects for development. Undoubtedly, this experience allowed me to develop and value audiovisual social responsibility.